Simulation of Salinity Intrusion from Arabian Gulf to Shatt Al-Arab River - HAMDAN, AHMED NASEH AHMED (Basrah Journal for Engineering Sciences, 2016)
This study is an attempt to determine the salinity intrusion from Arabian Gulf to Shatt Al-Arab River. One dimensional time dependent hydrodynamics model coupled with salinity model were applied and solved numerically by using the explicit finite difference method, a computer program was used to simulate the flow and the salinity concentration. “Total tide” software has been used to get an information about tide level in the day of field measurement, field measurement of salinity and tide velocity in Al-Fao Station was taken for a full tidal cycle and compared with the program results shows a good agreement between field measurement and numerical model results. Three sections were taken along the Shatt Al-Arab River to study the effect of salinity intrusion from the sea. It were found that the effect of salinity intrusion from the sea, reach a distance of a few kilometers upstream of Shatt Al-Arab mouth, but not farther than Abadan region. It is found that the salinity increased rapidly in the last of tidal period to a distance approximately equal 50 km downstream of Karun river or 10 km upstream of Al-Fao, and reach gradually to the salinity of the sea.